Model of Supply Chain Management based on the Application of Lean Tools and DDMRP to Decrease Returns in Retail SMEs - Salas Musso, Rodrigo Alonso (2022)
The retail industry is very supportive for the development of the country since they contribute 10.3% of the country’s GDP and it’s on constant growth. On the other hand, the emergence of the COVID-19 caused an increase in the digital consumption. This research consists of the implementation of Lean Manufacturing tools that have two tools of use that are standardized work and Poka Yoke. On the other hand, there is the DDMRP tool that helps the company with their supply chain management. Finally, with the results obtained, a certain improvement can be seen in the three indicators that were focused on greater detail. The first was the delayed orders due to stock breakage, which fell to 2.55%, reaching the target percentage. The other two indicators that did not reach their objectives were returns for errors and returns for damages that had a decrease of 1.24% and 3.89% respectively, but they still had a regular improvement that will have to be analyzed which will be the best implementation so that this time achieve the desired goals.